A Quantitative Evaluation on the Appearance Quality of Weld Line in RHCM Part. Issue 2 (8th May 2019) - Li, Jiquan; Li, Taidong; Xu, Fuyu; Jiang, Shaofei
Abstract : The appearance quality of plastic parts in weld line can be improved significantly through the Rapid Heating Cycle Molding (RHCM) process. However, there is no evaluation method for measuring the appearance quality of weld lines to determine whether they are in good or bad condition. In this study, the RHCM parts were molded with electric heating, and the total color difference dE of the CIE (Commission Internationale de L'Eclairage) Lab system was employed as the quantitative evaluation method for the appearance quality of weld line. The dE of weld lines under different heating temperature conditions was analyzed. The results indicate that the mold heating temperature significantly influences the appearance quality of weld lines, and the CIE Lab system accurately assesses the appearance quality of weld lines. Moreover, the experimental results further demonstrate that the lightness difference ΔL has a significant influence on the dE of weld lines in plastic parts, whereas the color differences Δa and Δb have only a slight influence.